Polymorphism in the thiopurine s-methyl transferase gene of Filipino patients from the Philippine General Hospital - Barile, Monique D.
Objectives: Inherited variation in the activity of Thipurine S-Methyltransferase (TPMT) is an important concern in thiopurine therapy. It has been shown that the frequency of the variation differs among ethnic populations, with limited data on Filipinos. The aims of this study are to determine the type and frequency of the most common TPMT polymorphisms in Filipino population and to estimate the cost or savings that maybe acquired when TPMT test may prevent adverse drug reaction (ADR) is conducted prior to thiopurine therapy. Methods: Eleven loci corresponding to 12 TPMT alleles were evaluated in 146 patients from the Philippine General Hospital (PGH) through Polymerase Chain reaction (PCR) and sequencing techniques. Afterwards, the cost of testing was analyzed using a hypothetical cohort of pediatric acute lymphoblastic leukemia (ALL) patients. Results: Four alleles were detected in the subjects namely: TPMT*1, TPMT*s, TPMT*3C and TPMT*8. They conferred frequencies of 71.58%, 24.32%, 3.4% and .34%, respectively. Additionally, a novel variant at the intronic region, NG _012137.1:g.21235delC was identified. The clinically significant alleles (i.e., TPMT*3C and TPMT *8) are expressed as heterozygous genotypes in 7.53% of the population. Savings from prevention of ADR may range from Php3,224.28 to Php12,388,210.03 depending on the severity and frequency of the event. However, only -4% of the population is estimated to benefit from the TPMT test. Conclusion: This study confirms presence of polymorphic TPMT gene in Filipino subjects, suggesting that genetically determined ADR maybe encountered in this population. Cost analysis indicates that significant amount maybe saved from averting ADR via TPMT testing. However, only a small portion of population may benefit from this test alone. It is anticipated that benefits from using molecular based tests will improve as more ADR associated genes and more robust technologies are introduced in the health facilities.